Reconocimiento preliminar sobre enfermedades del maíz en Centroamérica y Panamá - Schieber, E. (Instituto Interamericano de Cooperación para la Agricultura (IICA), 2025)
The author has used the opportunity offered by frequent visits to Central America and Panama, to observe diseases in corn, a crop that grows in diverse environments. These visits were made to temperate and cold zones, as well as sub-tropical and tropical areas, from Guatemala to Panama. Certain of the diseases encountered have not been recognized previously and this is the first description of them to appear in the literature of plant pathology on corn.